2019
DOI: 10.1002/ejoc.201901252
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Visible‐Light‐Mediated Hydrotrifluoromethylation of Unactivated Alkenes and Alkynes in Continuous Flow

Abstract: We report herein a novel photoredox‐catalyzed hydrotrifluoromethylation of unsaturated systems under continuous flow. This metal‐free method is easily broadened to other perfluoroalkyl groups (RF = CF3, CFCl2, CF2Br, C4F9) thanks to the use of sulfilimino iminiums as sources of ·RF radicals. The mild reaction conditions are compatible with unactivated alkenes bearing a wide range of functionalities, as well as with alkynes for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The use of fluorinated sulfilimino iminiums in a photocatalytic transformation in flow was described by Dagousset, Magnier, and co-workers (Scheme ). In a previous report in batch, the authors reported this class of compounds which provide perfluoroalkyl radical under light irradiation in the presence of an iridium­(III) catalyst for the first time . In flow, fluorinated sulfilimino iminiums were used to hydroperfluoroalkylate alkynes and alkenes.…”
Section: Flow Photochemistrymentioning
confidence: 99%
“…The use of fluorinated sulfilimino iminiums in a photocatalytic transformation in flow was described by Dagousset, Magnier, and co-workers (Scheme ). In a previous report in batch, the authors reported this class of compounds which provide perfluoroalkyl radical under light irradiation in the presence of an iridium­(III) catalyst for the first time . In flow, fluorinated sulfilimino iminiums were used to hydroperfluoroalkylate alkynes and alkenes.…”
Section: Flow Photochemistrymentioning
confidence: 99%
“…In addition, photochemical flow approaches have been developed with great success for functionalization reactions, such as halogenations [66][67][68][69], trifluoromethylations [70][71][72], oxygenations [73][74][75] and C-H activations [76][77][78]. All these applications showcase how continuous set-ups help to overcome limitations commonly encountered with classical photochemistry, and it is apparent that a variety of light sources as well as reactor configurations are exploited to best serve the intended chemical route.…”
Section: Remaining Challenges For Effectively Integrating Photoreactimentioning
confidence: 99%
“…The old Ciamiciamn reactions and their methodology had again become on the forefront of research with the advent of 'green' chemistry, where his methods have been found to fit easily with the requirements of that topic and have become a favorite ground for testing flow conditions [101][102][103][104][105][106][107] in microreactors and for photocatalytic processes including those involving visible light. Fig.…”
Section: Discussionmentioning
confidence: 99%